Appropriateness of the Use of the SCII-TPPSC for Anglophone and Francophone Canadian Populations - Chislet, Lise; Price, Adrienne; Mason, Gil; Lawson, Kerry (Canadian Journal of Counselling and Psychotherapy, 2011)
Holland's hexagonal model has been used to interpret scores of the Strong-Campbell Interest Inventory (SCII) and the Test de préférences professionnelles Strong Campbell(TPPSCC) with Anglophone and Francophone Canadian college populations ever since the introduction of the General Occupational Theme scales in 1974 and 1977 respectively. An examination of the appropriateness of the use of the theoretical model in organizing the General Occupational Theme scores of the SCII and the TPPSCC with Canadian populations is therefore highly = relevant and overdue. The fit of Holland's RIASEC model to the internal relationships among the General Occupational Theme scales was investigated for a combined sex, a male and a female U.S. General Reference sample (as reported in the SCCII manual), and for Anglophone and Francophone subjects in a combined sex, a male and a female sample by means of the KYST nonmetric multidimensional scaling analysis. For the combined sex samples and for all males, the SCII-TPPSC GOT scale fit to the hexagonal model was very appropriate. For Canadian Anglophone and Francophone females, the fit between the GOT scales with the hexagonal model was considerably better than for the U.S. female norming sample. Developmental issues such as the effect of age on the clustering of certain scales and the interpretation of their scores are discussed.